The Effect of Formal Versus Informal Job Security on Employee Involvement Programs - Preuss, Gil; Lautsch, Brenda (Relations industrielles / Industrial Relations, 2002)
SummaryThis study examines the effect of employee involvement and job insecurity on employee satisfaction and commitment. A data set incorporating information from employees, managers and government sources in fifteen hospitals in a single metropolitan region in the United States is used to test these issues. In contrast to previous research, we find that workers’ satisfaction and commitment persist as long as the form of employee involvement in place increases worker input and control in their jobs and as long as management is perceived to be making clear efforts to enhance the future security of workers’ jobs. Employee perception of management effort to maintain employment security, however, is based on past downsizing within the organization, thus raising the potential that continued downsizing will increase insecurity and therefore will decrease both employee desire to participate in decision-making, as well as employee satisfaction and commitment to the organization.